SOME RESPONSE OF CORN VARIETY ON ALUMINUM POISONING IN ADDITIONAL PHASE - Deo Palari; Tantri Palupi; Darussalam Darussalam (Fakultas Pertanian Universitas Tanjungpura, 2020)
Natural factors that often become obstacles in corn production are aluminum (Al) poisoning. Al poisoning is a major limiting factor for plant growth and yield, especially corn plants on dry land that reacts sourly in wet tropical regions. One other alternative that can be done is by using varieties that are well-adapted to the conditions of Al poisoning. Testing of varieties that are resistant to aluminum poisoning can be obtained by testing the germination phase. That’s phase is a fast alternative because it does not require a long time and environmental conditions can be compared to testing until the vegetative and generative phases.This study aims ware to determine the response of several maize varieties on the germination phase of aluminum poisoning. This research was conducted in June 2019 at the Laboratory of Agronomy and Climatology at the Faculty of Agriculture, Tanjungpura University, Pontianak. The experiment used in this study was a single randomized complete design of 5 maize varieties. The treatments used were A = Lamuru, B = Bay Bayur, C = Yellow Srikandi, D = Sukmaraga, E = Bhishma. Observation variables consisted of water content (%), germination (%), vigor index (%), growth rate (% / etmal), root length (cm), plumula length (cm) and normal seed dry weight (g).The results showed that the results of diversity analysis showed that several maize varieties in aluminum stress significantly affected the variable root length and normal seed dry weight, but it did not significantly affect the germination power, index vigor, growth speed, and length of the plumula. Keywords: aluminum, corn, germination